An in-depth analysis of comorbidities in the context of HIV burden, in a cohort of patients seeking healthcare at Khayelitsha facilities in 2016-2017 - Osei-Yeboah, Richard (Department of Integrative Biomedical Sciences (IBMS), 2023)
Introduction: Improvements in early detection of human immunodeficiency virus (HIV), linkage to treatment, and availability of antiretroviral therapy (ART) have contributed to increasing life expectancy for people living with HIV (PLHIV) in South Africa. These improvements have resulted in the decline of HIV cause-specific mortalities. In addition to existing tuberculosis burden in PLHIV, cases of chronic non-communicable diseases (NCDs) are increasing in the general population. Considering the ageing population of PLHIV in South Africa, it is important to understand their health needs, as well as identify potential drivers of comorbidities that may provide avenues for future interventions. This study aimed at exploring HIV and comorbidity profiles in a virtual cohort of a population of healthcare clients accessing care in public facilities in Khayelitsha, Cape Town. Methods: Routinely collected data for healthcare clients accessing care in public facilities in 2016/17 were obtained from the Western Cape Provincial Health Data Centre, and analysed to describe ascertained comorbidities, comparing the profiles of PLHIV and HIV-negative individuals. The risks of comorbidity occurrence in PLHIV, in the context of other comorbidities and HIV metrics such as ART duration, viral load and CD4 cell counts, including the contribution of comorbidities to unsuppressed viral load levels in PLHIV were explored. Findings: The findings show that accessing HIV care may lead to earlier ascertainment of common chronic NCDs – hypertension, diabetes, chronic kidney disease (CKD), cervical cancer in PLHIV, compared to HIV-negative clients. Analysis of routine health data suggests that ascertainment of comorbidities differs for healthcare clients due to sub-population differences including age, sex, HIV status and reasons for accessing care. Routine laboratory testing results for renal function reflect distinct healthcare experiences by age for healthcare clients with and without HIV. Analysis of routine data shows that presence of an existing comorbidity may contribute to the incidence of other comorbidities and unsuppressed viral load levels in PLHIV. Conclusion: From real life routine health data, this study has explored comorbidities profiles of PLHIV and HIV-negative clients and observed that routine health data could provide a better understanding of disease profiles, healthcare access and requirements for both PLHIV and HIV-negative clients.